Legal Certainty-Based Implementation of Exploration and Exploitation Authorization Permits in Iron Sand Mines - Fadil, Lalu Muhammad; Septyanun, Nurjannah; Erwin, Yulias; Harun, Rina Rohayu (JILPR Journal Indonesia Law and Policy Review, 2024)
Iron sand mining in the Dedalpak Block began in 2009 where the authority to grant mining permits ranging from mining business permits (IUP) exploration to mining business permits (IUP) for production operations was issued by the Regent of East Lombok by adhering to article 37 of Law Number 4 of 2009. However, with the enactment of Law Number 32 of 2014 Challenging Regional Governments, the authority of the iron sand mining permit was taken by the NTB Provincial Government, then with the presence of Law Number 3 of 2020 the authority for iron sand mining business licenses by PT. AMG was taken over by the Centre. In its implementation, iron sand mining by PT. AMG with the enactment of Law Number 3 of 2020 has a significant impact on the mining licensing process for iron sand production in the Dedalpak block of East Lombok, where the central government through the Director General of Energy and Mineral Resources requires thirteen conditions so that the IUP for production operations can be obtained by PT. AMG. The company, however, has not been able to meet five requirements, so its license was suspended. Another impact, the community in the Dedalpak block circle resisted by going to race through a series of protests for the mining to be closed, because it caused a large environmental impact.